Arctic security in an age of climate change / edited by James Kraska. - Kraska, James (Cambridge University Press, 2011)
This book examines Arctic defense policy and military security from the perspective of all eight Arctic states. In light of climate change and melting ice in the Arctic Ocean, Canada, Russia, Denmark (Greenland), Norway and the United States, as well as Iceland, Sweden and Finland, are grappling with an emerging Arctic security paradigm. This volume brings together the world's most seasoned Arctic political-military experts from Europe and North America to analyze how Arctic nations are adapting their security postures to accommodate increased shipping, expanding naval presence, and energy and mineral development in the polar region. The book analyzes the ascent of Russia as the first 'Arctic superpower', the growing importance of polar security for NATO and the Nordic states, and the increasing role of Canada and the United States in the region.